Ecological risk assessment and prediction of riparian zones in the Jiangsu section of the Yangtze River from a spatiotemporal perspective - Zihan Zhu; Cheng Zhang; Yangyang Lu; Jian Ye; Guohua Fang; Changran Sun; Yun Yang (Ecological Indicators)
As transitional areas between rivers and land, riparian zones are important for economic and social development and ecological environmental protection. However, urbanisation has significantly increased the ecological risks in these areas. Focusing on the Yangtze River riparian zone in Jiangsu Province, an ecological risk assessment system with 20 indicators was developed based on a systematic analysis of the ecological risk exposure–response process. The temporal and spatial characteristics of ecological risks in the riparian zone from 2003 to 2023 were analysed using the ecological risk composite index model, Moran index, and Getis-Ord Gi* cold hotspot analysis method, while ecological risks for 2028 and 2033 were predicted using the Grey–Markov chain and PLUS models. The findings indicate that (1) high ecological risk areas were mainly concentrated in the Nanjing, Nantong, and Suzhou River sections, with key risk factors including development intensity, pollutant discharge intensity, and ecological riparian retention rate. (2) From 2003 to 2023, ecological risk displayed an initially increasing and then decreasing trend, which reflects the effectiveness of ecological protection policies. However, industrial areas still face increasing risks. (3) Ecological risks exhibited strong positive correlation characteristics, with zoning policies enhancing the clustering effect. The cold hotspot analysis identified three large and two small hotspot areas. (4) By 2028 and 2033, ecological risk will likely show an overall declining and locally increasing trend, necessitating timely policy adjustments to address the rising ecological risks.